Answer:
Step-by-step explanation:
<u>Actual question is:</u>
- logf 4(3d) + log4 1 = log4 3d
<u>Solution:</u>
- logf 4 + logf (3d) + 0 = log4 (3d)
- logf 4 + logf (3d) = log4 (3d)
<u>If we assume f = 4, then</u>
- log4 4 + log4 (3d) = log4 (3d)
- log4 4 = 0
but log4 4 = 1
Therefore the statement is False
Answer:
two 2
Step-by-step explanation:
First you divide the five over six into the two over three, then you add the quotient of that problem to three over four and the sum is your answer.
Answer:
there are 125 cars in the parking lot
Step-by-step explanation:
Answer:
i dont know
Step-by-step explanation:
Using Pythagorean’s theorem, the side length is sqrt(89)